Understanding farm generational renewal and its influencing factors in Europe. (August 2021) - Coopmans, Isabeau; Dessein, Joost; Accatino, Francesco; Antonioli, Federico; Bertolozzi-Caredio, Daniele; Gavrilescu, Camelia; Gradziuk, Piotr; Manevska-Tasevska, Gordana; Meuwissen, Miranda; Peneva, Mariya; Pettit, Andrea; Urquhart, Julie; et al.
Abstract: Understanding the complex process of generational renewal (GR) in agriculture is essential for supporting the continuation of farming. This paper demonstrates how multiple factors, simultaneously and through their mutual interactions, influence GR and related individual decision-making processes. Results originated from 155 in-depth interviews performed on 85 farms in eleven European regions, and were triangulated with the literature. Our analysis, combining inductive and deductive approaches, revealed three conceptual phases (successor identity formation, farm succession process, and farm development) and fourteen factors important to understand GR. We elaborate how these factors interact, hence exert their impact on (one of) the phases in a complex and variable way. Implications highlight potential pitfalls and opportunities for attracting people into agriculture. Although policy-makers should be aware of their limited ability to affect GR by targeting the first phase, we propose some ideas that would complement current existing measures acting on the third phase. Highlights: Attracting people to farming demands profound understanding of generational renewal. We study decisions relating to generational renewal on 85 farms in 11 EU regions. Fourteen factors can impact three phases of the farm generational renewal process. Current policy might miss its goals because of targeting the wrong phase. Future policy must better address relevant (interplay of) impact factors.